Multi-criteria decision analysis of Circular Economy performance in the Baltic States: a comparative evaluation - Štreimikienė, Dalia; Bathaei, Ahmad; Baležentis, Tomas; Štreimikis, Justas (Journal of Business Economics and Management, 2025)
This study embarks on a comparative evaluation of Circular Economy (CE) performance in the Baltic States (Latvia, Lithuania, and Estonia) using a robust multi-criteria decision-making (MCDM) framework. Drawing on 22 key indicators, the research applies the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to systematically rank the country-level CE implementation across five thematic dimensions: production and consumption, waste management, secondary raw materials, competitiveness and innovation, and global sustainability. The results reveal that Latvia ranks highest, followed by Lithuania and Estonia, underscoring significant differences in waste management efficiency, investment in CE sectors, and material self-sufficiency. The main contribution of this paper lies in the development of a comprehensive, quantitative benchmarking framework that integrates multiple CE indicators and MCDM methods to assess national performance in a data-driven manner. The methodology developed here can serve as a replicable model for CE assessment in other regional or national contexts.